CLUSTER DEVELOPMENT STRATEGY IN THE CONTEXT OF THE "KEY NATIONAL CLUSTER" COMPETITION - Haberla, Marcin (Acta Scientiarum Polonorum. Oeconomia, 2016)
The role of cluster development strategy is discussed, in the context of Polish "Key National Cluster" (KKK) competition. According to formal KKK regulations, the status of a key national cluster can only be granted to those selected few clusters which fulfill the detailed preconditions stated in the document, such as the postulate to offer support for regional specialisation. The paper places emphasis on the significance of management, as an area of great impact in the determination of key status of clusters. In fact, the KKK competition is designed to evaluate formal strategies of cluster development in a multi-stage approach, including expert feasibility studies. In addition, the paper discusses changes in the national approach to cluster policy, as observed in the statutory activities of Polish cluster support system over the last few years. Those changes were dictated by the need to offset the general tendency to place emphasis on the quantitative aspects of development, as opposed to the postulated focus on the quality and competitiveness of cluster structures.